Genetic Variations in Schistosoma Haematobium, Resistance and Reinfection in the Greater Accra Region - Forson, P.O. (University Of Ghana, 2017)
Background: Schistosomiasis is among the major parasitic diseases following malaria in the category of neglected tropical diseases (NTD) especially in Africa sub-Saharan region. About 93% of Schistosomiasis is believed to occur in Africa. The genus Schistosoma is the parasitic trematode worm responsible for this disease. Schistosoma haematobium is responsible for causing Urogenital Schistosomiasis. The WHO recommended drug for schistosomiasis is Praziquantel (a single dose of 40mg/kg). Resistance of Schistosomiasis using Praziquantel (PZQ) has been reported in Egypt and Senegal. However, in endemic areas, reinfection after treatment is common. Genetic variants in Schistosomes have been observed in countries like Mali and Sudan. Presently in Ghana little is known about trends of genetic variants, as well as the possibility of resistance development and reinfection. Aim: The aim of this study is to determine genetic variation in Schistosoma haematobium (ITS2, NAD1, COX1), assessment of resistance and reinfection. Methodology: Urine samples of school children were obtained with consents from parents and guardians in the two communities (Zenu and Weija) in the Greater Accra region. Microscopy with egg count as well as viability test (modified hatchability technique, vital stains, and fluorescent microscopy) was performed on the spun urine sediments after macroscopic examination. The study procedure included a follow up collection of urine samples after treatment to assess resistance and reinfection. Genetic variation was assessed from sequences of the PCR amplified products (ITS2, NAD1) by comparing with sequences from other countries. Results: The percentage reinfection was 10.4% and there was no resistance observed in this study. The mean percentage viability of all the methods used were 70% and 30% in live and dead eggs respectively at baseline. At post-treatment, the percentage viability of live and dead eggs was 13.3% and 86.6% respectively. For the ITS 2 sequences, there was genetic variation from the Kenyan strain and for the NAD 1 sequences it varied from Madagascar, Mauritius and Tanzania. Conclusion: Reinfection was recorded among the study participants however there was no resistance observed. There was effect of treatment on the viability of Schistosoma haematobium eggs using the modified hatchability technique which was complemented by the vital stains and the fluorescent microscopy. Genetic variants were identified in relation to other countries.
Keywords: Schistosoma Haematobium; Africa sub-Saharan region.; Praziquantel